Sense Relations in Language Learning - Winiharti, Menik (Humaniora, 2010)
Studying a language cannot be separated from studying the meaning of that language because when one is learning a language he/she is also learning the meaning of the language. The meaning of a language can be seen from its relation between words, i.e. the sense of one word is related to the sense of another. In this case there are two major groups of sense relations. The first group is the sense relations with regard to the sameness as synonymy. The second one is the sense relations of oppositeness as antonymy. This paper is to discuss both kinds of sense relations since they are important in semantics.